Digitalisering av Mitt Hälsodokument - Omid,Sahar; Pihl,Victor (2022)
Since a brain injury often can affect the memory in some ways it is sometimes hard to remember to bring that piece of paper. And since more and more people of the aging population carry a cellphone daily - the need for a digital alternative to My health document became more apparent. In this project we got the task of digitalizing My health document. We confirmed the need for a digital solution by collecting information through interviews with patients, medical personnel and by collecting data from a form. This information were analyzed and converted into different prototypes of a mobile application resulting in a final protype showing the benefits of a digital application to My health document.